Diagnostic precision of mentally estimated home blood pressure means. Issue 4 (August 2018) - Ouattara, Franck Olivier; Laskine, Mikhael; Cheong, Nathalie Ng; Birnbaum, Leora; Wistaff, Robert; Bertrand, Michel; van Nguyen, Paul; Kolan, Christophe; Durand, Madeleine; Rinfret, Felix; Lamarre-Cliche, Maxime
Abstract : Context: Paper home blood pressure (HBP) charts are commonly brought to physicians at office visits. The precision and accuracy of mental calculations of blood pressure (BP) means are not known. Methods: A total of 109 hypertensive patients were instructed to measure and record their HBP for 1 week and to bring their paper charts to their office visit. Study section 1: HBP means were calculated electronically and compared to corresponding in-office BP estimates made by physicians. Study section 2: 100 randomly ordered HBP charts were re-examined repetitively by 11 evaluators. Each evaluator estimated BP means four times in 5, 15, 30, and 60 s (random order) allocated for the task. BP means and diagnostic performance (determination of therapeutic systolic and diastolic BP goals attained or not) were compared between physician estimates and electronically calculated results. Results: Overall, electronically and mentally calculated BP means were not different. Individual analysis showed that 83% of in-office physician estimates were within a 5-mmHg systolic BP range. There was diagnostic disagreement in 15% of cases. Performance improved consistently when the time allocated for BP estimation was increased from 5 to 15 s and from 15 to 30 s, but not when it exceeded 30 s. Conclusion: Mentally calculating HBP means from paper charts can cause a number of diagnostic errors. Chart evaluation exceeding 30 s does not significantly improve accuracy. BP-measuring devices with modern analytical capacities could be useful to physicians. Abstract : Supplemental Digital Content is available in the text.